2006
DOI: 10.1002/hed.20335
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nutrition support on treatment outcome in patients with locally advanced head and neck squamous cell cancer treated with definitive radiotherapy: A secondary analysis of RTOG trial 90-03

Abstract: In this study, the largest prospective evaluation of nutrition data in treated patients with cancer, BNS was associated with inferior treatment outcome in the patients with HNSCC undergoing XRT. These results should be considered hypothesis generating and encourage prospective clinical research and identification of the mechanisms underlying this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 39 publications
1
54
0
5
Order By: Relevance
“…For example, in a prospective study of patients with HNSCC undergoing RT, Ravasco and colleagues found that nutritional counseling with regular foods was superior to only adding nutritional supplements in maintaining quality of life during and at 3 months post-RT, but the impact of these interventions on weight was not reported [44]. In a large retrospective review of patients on RTOG 90-03, investigators performed a secondary analysis of patients with HNSCC treated with four different radiation strategies, Rabinovitch and colleagues found that beginning nutritional supplementation before starting RT was a negative prognostic indicator for locoregional failure and death, HR 1.47, 95 % CI 1.21-1.79, p < .0001 and HR 1.41, 95 % CI 1.19-1.67, p < .0001, respectively [45]. Given the retrospective nature of this analysis, nutritional supplement was likely initiated pre-RT in patients who presented with weight loss at diagnosis.…”
Section: Main Textmentioning
confidence: 99%
“…For example, in a prospective study of patients with HNSCC undergoing RT, Ravasco and colleagues found that nutritional counseling with regular foods was superior to only adding nutritional supplements in maintaining quality of life during and at 3 months post-RT, but the impact of these interventions on weight was not reported [44]. In a large retrospective review of patients on RTOG 90-03, investigators performed a secondary analysis of patients with HNSCC treated with four different radiation strategies, Rabinovitch and colleagues found that beginning nutritional supplementation before starting RT was a negative prognostic indicator for locoregional failure and death, HR 1.47, 95 % CI 1.21-1.79, p < .0001 and HR 1.41, 95 % CI 1.19-1.67, p < .0001, respectively [45]. Given the retrospective nature of this analysis, nutritional supplement was likely initiated pre-RT in patients who presented with weight loss at diagnosis.…”
Section: Main Textmentioning
confidence: 99%
“…[83][84][85][86] One study of upper GI cancer patients indicated less weight loss and fewer treatment interruptions in patients who received EN prior to radiation therapy (XRT). 83 Two studies in head and neck cancer patients failed to demonstrate reduced weight loss 84 ; furthermore, worse survival 85 Rationale: NST is appropriate in patients receiving active anticancer treatment who are malnourished and who will be unable to absorb adequate nutrients for a prolonged period of time to minimize risk of poor outcomes associated with malnutrition. Seven to fourteen days seems an appropriate definition of "prolonged period of time"; this time period is referred to in many studies, although there are no well designed studies that specifically address this issue.…”
Section: Practice Guidelines and Rationalesmentioning
confidence: 99%
“…81,82 The strength of this guideline is tempered by the fact that the best and largest RCT is limited to a head and neck population receiving radiation. 85 See Table A6. 7. The palliative use of nutrition support therapy in terminally ill cancer patients is rarely indicated.…”
Section: Practice Guidelines and Rationalesmentioning
confidence: 99%
“…7,[12][13][14] Several studies have shown nutritional interventions in HN cancer patients to have a positive impact on their nutritional status, quality of life, and treatment compliance. [15][16][17] In HN cancer patients, several factors contribute to weight loss before, during, and after treatment. Weight loss is usually attributed to the physiological abnormalities associated with the tumor (because of obstruction and interference with swallowing), the tumor host response (such as chronic inflammation and cytokine production), and the adverse effects of cancer treatments.…”
mentioning
confidence: 99%